The sirens' call [large type] : how attention became the world's most endangered resource - Hayes, Chris, 1979 February 28- (Random House Large Print, 2025)
"From the NYT-bestselling author and television and podcast host, a powerful wide-angle reckoning with how the assault from attention capitalism on our minds and our hearts has reordered our politics and the very fabric of our society"--